2019
DOI: 10.1186/s12875-019-0972-1
|View full text |Cite
|
Sign up to set email alerts
|

Shared medical appointments and patient-centered experience: a mixed-methods systematic review

Abstract: Background Shared medical appointments (SMAs), or group visits, are a healthcare delivery method with the potential to improve chronic disease management and preventive care. In this review, we sought to better understand opportunities, barriers, and limitations to SMAs based on patient experience in the primary care context. Methods An experienced biomedical librarian conducted literature searches of PubMed, Cochrane Library, PsycINFO, CINAHL, Web of Science, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 52 publications
(95 reference statements)
1
58
0
Order By: Relevance
“…The themes identified from professionals are consistent with the literature regarding patients who have participated in group consultations, which has shown positive data relating to the patient–clinician dynamic, improved satisfaction, and a perception that staff appear less hurried. 12 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The themes identified from professionals are consistent with the literature regarding patients who have participated in group consultations, which has shown positive data relating to the patient–clinician dynamic, improved satisfaction, and a perception that staff appear less hurried. 12 …”
Section: Discussionmentioning
confidence: 99%
“…Evidence from systematic reviews and meta-analyses suggests that group consultations are effective in improving clinical outcomes, such as haemoglobin A1C (HbA1c) and blood pressure in diabetes, and are associated with positive patient experience measures, although questions remain about the impact on other clinical outcomes and the feasibility and cost-effectiveness of the approach. 10 , 11 Although few studies have cited barriers to implementation, 12 a lack of confidence and skills in facilitation, along with an ingrained, established model of consultation, are suggested reasons for hesitancy regarding the approach. 9 , 13 , 14 However, a paucity of evidence exploring implementation in UK general practice exists.…”
Section: Introductionmentioning
confidence: 99%
“…Data on the use of SMAs continue to accumulate, particularly in the field of diabetes . Reviews of such research have concluded that while there are indications of improved outcomes in patients managed with SMAs, the small size and heterogeneity of studies thus far does not allow for conclusions to be drawn from the collective body of research …”
Section: Introductionmentioning
confidence: 99%
“…17 SMAs are usually conducted over a 2-hour period. 22 It is important to note that each SMA requires private time for each patient with the provider. During this time, the patient will have the opportunity to discuss issues they may not feel comfortable discussing in the group format.…”
Section: Lmsma Structure and Logisticsmentioning
confidence: 99%